Supersymmetry breaking effects using the pure spinor formalism of the superstring - Berkovits, Nathan [UNESP]; Witten, Edward (Springer, 2014)
The SO(32) heterotic superstring on a Calabi-Yau manifold can spontaneously break supersymmetry at one-loop order even when it is unbroken at tree-level. It is known that calculating the supersymmetry-breaking effects in this model gives a relatively accessible test case of the subtleties of superstring perturbation theory in the RNS formalism. In the present paper, we calculate the relevant amplitudes in the pure spinor approach to superstring perturbation theory, and show that the regulator used in computing loop amplitudes in the pure spinor formalism leads to subtleties somewhat analogous to the more familiar subtleties of the RNS approach.
Keywords: Supersymmetry Breaking; Superstrings and Heterotic Strings